Improving Discipline in Children Aged 5-6 Years through Serial Storybooks: Classroom Action Research at PAUD Nusa Indah V - Nuraisyah, Siti; Darmiyanti, Astuti; Rochimah, Nur (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Discipline in early childhood is reflected in children’s emerging ability to follow routines, comply with agreed rules, complete activities, and use socially appropriate behavior in daily learning. This study examined the use of serial storybooks to improve discipline among children aged 5–6 years at PAUD Nusa Indah V. The study employed collaborative classroom action research based on the Kemmis–McTaggart cycle of planning, action, observation, and reflection. Fourteen children in Kindergarten B (10 boys and 4 girls) participated. The intervention was implemented in two cycles, with four meetings in each cycle. The storybook series addressed three recurring domains of classroom discipline: time discipline, learning/activity discipline, and etiquette/routine discipline. Data were collected through structured observation, documentation, and field notes and analyzed using descriptive quantitative comparisons and qualitative reflection across cycles. The mean discipline achievement was 40.10% at pre-action, increased to 52.30% in Cycle I, and reached 77.02% in Cycle II. Thus, the increase was 12.20 percentage points from pre-action to Cycle I and 24.72 percentage points from Cycle I to Cycle II, for an overall gain of 36.92 percentage points. Qualitative observations indicated improved punctuality, rule-following, task completion, classroom routines, and polite behavior, accompanied by greater attention and engagement during storytelling. The findings suggest that serial storybooks can function as a developmentally appropriate, low-cost medium for repeatedly modeling expected behavior and supporting classroom habituation. Because the study involved one small class without a comparison group, the findings should be interpreted as evidence of classroom improvement rather than population-level causal effects.